Coefficient Estimates for Certain Classes of Bi-Univalent Functions - Jay M. Jahangiri; Samaneh G. Hamidi (International Journal of Mathematics and Mathematical Sciences)
A function analytic in the open unit disk is said to be bi-univalent in if both the function and its inverse map are univalent there. The bi-univalency condition imposed on the functions analytic in makes the behavior of their coefficients unpredictable. Not much is known about the behavior of the higher order coefficients of classes of bi-univalent functions. We use Faber polynomial expansions of bi-univalent functions to obtain estimates for their general coefficients subject to certain gap series as well as providing bounds for early coefficients of such functions.